Trophic interactions between native and introduced fish species in a littoral fish community - M. Monroy; A. Maceda‐Veiga; N. Caiola; A. De Sostoa (Journal of Fish Biology, 2014)
The trophic interactions between 15 native and two introduced fish species, silverside Odontesthes bonariensis and rainbow trout Oncorhynchus mykiss , collected in a major fishery area at Lake Titicaca were explored by integrating traditional ecological knowledge and stable‐isotope analyses ( SIA ). SIA suggested the existence of six trophic groups in this fish community based on δ 13 C and δ 15 N signatures. This was supported by ecological evidence illustrating marked spatial segregation between groups, but a similar trophic level for most of the native groups. Based on Bayesian ellipse analyses, niche overlap appeared to occur between small O . bonariensis ( Orestias ispi and large O . bonariensis (39%) or O . mykiss (19·7%). In addition, Bayesian mixing models suggested that O . ispi and epipelagic species are likely to be the main prey items for the two introduced fish species. This study reveals a trophic link between native and introduced fish species, and demonstrates the utility of combining both SIA and traditional ecological knowledge to understand trophic relationships between fish species with similar feeding habits.

Life‐history traits of the stone loach Barbatula barbatula - D. Vinyoles; A. De Sostoa; C. Franch; A. Maceda‐Veiga; F. Casals; N. Caiola (Journal of Fish Biology, 2010)
The life‐history tactics of the stone loach Barbatula barbatula were studied in a Mediterranean‐type climate stream (Matarranya River) located in the Ebro River basin (north‐east Spain). Maximum observed ages were 2+ years in both sexes (1% of individuals), although only 0+ and 1+ year age groups were well represented. It is the lowest longevity reported for this species in its entire distribution. The seasonal growth period started in June and continued until November, but the pattern observed was different to northern populations. Barbatula barbatula in the Matarranya River was a multiple spawner, releasing small batches of oocytes between April and June. The fecundity of females was higher and the size of oocytes smaller in 1984 than in 1985. The relative fecundity (number of ripening and ripe oocytes g −1 of fish) was lower than in northern European populations. The role of the particular environmental conditions of a Mediterranean stream was discussed in relation to the life‐history tactics of B. barbatula .

Assessing perturbation of river fish communities in the Iberian Ecoregion - T. FERREIRA; N. CAIOLA; F. CASALS; J. M. OLIVEIRA; A. DE SOSTOA (Fisheries Management and Ecology, 2007)
A spatially based approach was used to analyse the response of fish‐based metrics to human impacts in the Iberian Peninsula. A fish‐based typology was established that distinguished one salmonid type (fish assemblages dominated by Salmo trutta fario L.), two mixed types ( S. trutta fario associated with different cyprinids) and six cyprinid types (dominated by different species of barbel [ Barbus spp.], nase [ Chondrostoma spp.] or chub [ Leuciscus spp.]). These types broadly correspond to different forms of ecosystem functioning, ranging from the cold, northern and high altitude sections to warmwater, lowland and southern sections. Twenty metrics were identified that responded to disturbance – four to 14 per fish type. The highest correlations were −0.795 for abundance of Squalius sp. and segment (localised) disturbance and 0.754 for abundance of limnophilic specimens and water quality disturbance. Disturbance of segment, habitat and hydrological regime yielded more metric responses in western Iberian fish types, while that of habitat and water quality gave more in north‐eastern Iberian fish types. Global (catchment scale) disturbance generally gave more responsive metrics and higher correlations than partial disturbances. All guilds were represented and a number of metrics were responsive across fish types – namely native species, alien abundance, water column (natives), eurytopic and invertivorous (natives). However, several metrics were only reactive in one or a few types, such as benthic and S. trutta fario in north‐western mixed fish type. Different trends in metric reaction occurred for total abundance in north‐western mixed fish type, and for eurytopic and phytophilic (natives) in the north‐eastern fish types.

Ecological traits of fish assemblages from Mediterranean Europe and their responses to human disturbance - T. FERREIRA; J. OLIVEIRA; N. CAIOLA; A. DE SOSTOA; F. CASALS; R. CORTES; A. ECONOMOU; S. ZOGARIS; D. GARCIA‐JALON; M. ILHÉU; F. MARTINEZ‐CAPEL; D. PONT; et al. (Fisheries Management and Ecology, 2007)
Mediterranean river systems are characterised by more diverse fish assemblages and regional ecological processes compared with the rest of Europe. A data set from Mediterranean France, Iberia and Greece (∼2000 sites) was used to describe the characteristics of fish assemblages, explore their responses to anthropogenic disturbance and analyse the implications for river quality assessment. There was a southwards decline in species richness per site, but endemicity and proportion of alien species increased. Sites in the eastern Mediterranean had higher endemicity, lower site richness and lower number of alien species than sites in western Mediterranean Europe. Assemblage composition differed between Mediterranean sub‐regions, but was dominated by three major fish types: a salmonid fish type common throughout the study area and two cyprinid‐dominated fish types (in some sub‐regions, Salmo trutta L. is present but not numerically dominant), corresponding to a gradient in hydrological and temperature regimes. Metric responses to perturbation were compared with those found at the European (larger scale) and basin (smaller scale) levels. Overall metric response was weaker in this Mediterranean application. The best responses to human pressure were usually obtained with abundance‐based metrics and included the contribution of naturalised alien species. Some widespread alien species contributed to the response to anthropogenic alteration (notably Cyprinus carpio L. and Lepomis gibbosus (L.)).

Spatially based methods to assess the ecological status of riverine fish assemblages in European ecoregions - S. SCHMUTZ; A. MELCHER; C. FRANGEZ; G. HAIDVOGL; U. BEIER; J. BÖHMER; J. BREINE; I. SIMOENS; N. CAIOLA; A. DE SOSTOA; M. T. FERREIRA; J. OLIVEIRA; et al. (Fisheries Management and Ecology, 2007)
The objective was to develop spatially based (type‐specific) methods to assess the ecological status of European rivers according to the EU Water Framework Directive. Some 15 000 samples from about 8000 sites were pre‐classified within a five‐tiered classification system based on hydromorphological and physico‐chemical pressures. The pre‐classification was used to identify reference conditions and to calibrate the assessment methods. Clustering reference sites based on relative species composition resulted in 60 fish assemblage types within 11 of the ecoregions under study. Discriminant function analyses (DFAs) were employed to identify environmental parameters characterising fish assemblage types; altitude, river slope, wetted width, mean air temperature and distance from source were the principal predictors. These environmental parameters were used to assign impacted sites with altered fish assemblage composition to the reference fish assemblage type. Metrics (fish assemblage descriptors) responding to human pressures were selected based on correlation and DFAs. Assessment methods were developed for 43 fish assemblage types. Metrics based on individual sentinel species were more often used in type‐specific methods than metrics related to reproduction, habitat and feeding. Metrics based on long‐distance migrants and potamodromous species were more sensitive to human pressures than overall composition metrics, e.g. total number of species. Only some of the tested metrics showed pressure‐specific responses, i.e. reacted to one type of pressure but not to others. Insectivorous, intolerant and lithophilic species exclusively responded (decreased) to chemical and hydromorphological pressures in 14–19%. Omnivorous species was the only metric type that showed a consistent reaction (increase) to continuum disruptions in 25% of the cases. Accuracy of methods based on cross‐validation with pre‐classification varied between 47% and 98% (mean 81%) when contrasting calibration data set (class 1 and 2) with degraded sites (class 3, 4 and 5).

First record of the Asiatic cyprinid Pseudorasbora parva in the Iberian Peninsula - N. Caiola; A. de Sostoa (Journal of Fish Biology, 2002)
Pseudorasbora parva is recorded for the first time in the Iberian Peninsula. Its presence in the River Ebro delta is probably due to involuntary introduction.